Prealgebra and introductory algebra - Martin-Gay, Elayn ([Boston] : Prentice-Hall, 2011)
This book is written in response to the needs of those teaching combined courses. Specific care was taken to ensure that all core topics of an introductory algebra course are covered and that students have the most up-to-date, relevant text preparation for future courses.
Chapter1. The whole numbers -- Chapter2. Integers and introduction to solving equation -- Chapter3. Solving equations and problem solving -- Chapter4. Fractions and mixed numbers -- Chapter5. Decimals -- Chapter6. Ratio, proportion and percent -- Chapter7.Graphs and triangle applications -- Chapter8. Geometry and measurements -- Chapter9. Equations, inequalities and problem solving -- Chapter10. Exponents and polynomials -- Chapter11. Factoring polynomials -- Chapter12. Rational expressions -- Chapter13. Graphing equations and inequalities -- Chapter14. Systems of equation -- Chapter15. Roots and radicals -- Chapter16. Quadratic equations .
Includes index.
Keywords: PREALGEBRA